CD19-Targeted Immunotherapies for Diffuse Large B-Cell Lymphoma - Gambella, Massimiliano; Carlomagno, Simona; Raiola, Anna Maria; Giannoni, Livia; Ghiggi, Chiara; Setti, Chiara; Giordano, Chiara; Luchetti, Silvia; Serio, Alberto; Bo, Alessandra; Falco, Michela; Della Chiesa, Mariella; et al. (Frontiers in Immunology, 2022)
Surgical resection, chemotherapy and radiotherapy were, for many years, the only available cancer treatments. Recently, the use of immune checkpoint inhibitors and adoptive cell therapies has emerged as promising alternative. These cancer immunotherapies are aimed to support or harness the patient’s immune system to recognize and destroy cancer cells. Preclinical and clinical studies, based on the use of T cells and more recently NK cells genetically modified with chimeric antigen receptors retargeting the adoptive cell therapy towards tumor cells, have already shown remarkable results. In this review, we outline the latest highlights and progress in immunotherapies for the treatment of Diffuse Large B-cell Lymphoma (DLBCL) patients, focusing on CD19-targeted immunotherapies. We also discuss current clinical trials and opportunities of using immunotherapies to treat DLBCL patients.